2002
DOI: 10.1002/art.10234
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation of ITGAL (CD11a) regulatory sequences in systemic lupus erythematosus

Abstract: Objective. Inhibition of T cell DNA methylation causes autoreactivity in vitro and a lupus-like disease in vivo, suggesting that T cell DNA hypomethylation may contribute to autoimmunity. The hypomethylation effects are due, in part, to overexpression of lymphocyte function-associated antigen 1 (LFA-1) (CD11a/CD18). Importantly, T cells from patients with active lupus have hypomethylated DNA and overexpress LFA-1 on an autoreactive subset, suggesting that the same mechanism could contribute to human lupus. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
215
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 272 publications
(228 citation statements)
references
References 34 publications
10
215
3
Order By: Relevance
“…In other studies, our group has used bisulfite sequencing and regional methylation of reporter constructs to characterize how DNA methylation inhibitors and lupus increase CD11a and perforin expression. We found that demethylation of sequences flanking the CD11a promoter increase CD11a expression in vitro and in lupus (12). Similarly, demethylation of a region linking an enhancer and minimal promoter, located 600-800 bp 5Ј of the perforin transcription start site, is responsible for the increase in perforin in vitro and in lupus, although methylation changes also occur elsewhere but are transcriptionally irrelevant (8,9).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In other studies, our group has used bisulfite sequencing and regional methylation of reporter constructs to characterize how DNA methylation inhibitors and lupus increase CD11a and perforin expression. We found that demethylation of sequences flanking the CD11a promoter increase CD11a expression in vitro and in lupus (12). Similarly, demethylation of a region linking an enhancer and minimal promoter, located 600-800 bp 5Ј of the perforin transcription start site, is responsible for the increase in perforin in vitro and in lupus, although methylation changes also occur elsewhere but are transcriptionally irrelevant (8,9).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the same LFA-1 and perforin regulatory sequences were shown to be demethylated in CD4ϩ T cells from patients with active SLE as in T cells treated with 5-azaC or procainamide (8,12). Together, these studies suggest that T cell DNA hypomethylation may be fundamental to the pathogenesis of autoimmunity in the adoptive transfer model (4,5) and in humans with drug-induced and idiopathic lupus.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…26 Further, CD4+ T cells from patients with active lupus demethylate the same regulatory sequences, overexpress the same genes, and display the same autoreactive Mø killing and B cell overstimulation as cells demethylated in vitro with 5-azacytidine, procainamide and hydralazine. 17,27,28 Together, these observations suggest that T-cell DNA demethylation may contribute to the development of idiopathic and some forms of drug-induced lupus.…”
Section: Introductionmentioning
confidence: 90%
“…There is evidence that epigenetic mechanisms may have a role in autoimmune diseases, such as systemic lupus erythematosus where there is hypo-methylation of regulatory regions of pro-inflammatory genes, such as IL-6 and IL-4 in T cells. 13,14 Histone hypomethylation and hypoacetylation in CD4 þ cells from systemic lupus erythematosus patients has also been demonstrated. 15 DNA and histone H3K9 methyla- Odds Ratio (95% confidence interval) Figure 2 Odds ratio meta-analysis plot of rs11062385 in JARID1A (fixed effects).…”
Section: Resultsmentioning
confidence: 93%